2023
DOI: 10.3390/v15010221
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Hepatocellular Carcinoma in Patients with Chronic Hepatitis C Treated with Direct-Acting Antivirals

Abstract: Background: Conflicting data regarding the incidence of hepatocellular carcinoma (HCC) after cure of HCV infection with direct-acting antivirals (DAAs) remains. We investigated the incidence and risk factors to HCC after treatment with DAAs followed up for five years. Methods: A total of 1075 HCV patients ≥ 18 years were treated with DAAs from 2015 to 2019 and followed until 2022. Ultrasonography was performed before DAAs and each 6 months thereafter. Results: Of the total, 51/1075 (4.7%) developed HCC in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In this new DAA era, a prospective study suggested that in cirrhotic patients achieving SVR by DAA treatment reduces HCC incidence over time. Despite this, the risk of HCC after SVR with DAA remains high, and this residual risk is a relevant clinical problem [7][8][9][10].…”
Section: Hepatitis C Virus (Hcv) Is Still One Of the Leading Causes O...mentioning
confidence: 99%
“…In this new DAA era, a prospective study suggested that in cirrhotic patients achieving SVR by DAA treatment reduces HCC incidence over time. Despite this, the risk of HCC after SVR with DAA remains high, and this residual risk is a relevant clinical problem [7][8][9][10].…”
Section: Hepatitis C Virus (Hcv) Is Still One Of the Leading Causes O...mentioning
confidence: 99%